Kontinuitet og forandring i statens mål- og resultatstyringskoncept - Kristiansen, Mads Bøge (Politik, 2015)
This article analyses the development process of the Management by Objectives and Results (MBOR) dis- course over time in central government in Denmark. e article shows that MBOR has been marked by continuity since its introduction in the 1980s, and has become a central element in the steering and man- agement of agencies in central government. Nevertheless, gradual changes that have altered the direction of the MBOR discourse over time can also be identi ed. e direction changes from autonomy and a simple MBOR system in the early years towards more control and a more comprehensive system in the 1990s, and back again toward more autonomy and a less comprehensive MBOR system in recent years. In the nal sec- tion of the paper explanations of the development patterns are discussed.